Penggunaan lahan dan deforestasi di Kabupaten Bogor - Abdul Mukti (Institute for Advanced Science, Social, and Sustainable Future, 2023)
One of the causes of climate change is deforestation. Apart from that, deforestation also causes a significant decrease in the number of species for the biodiversity that lives in it (Sutarno et al., 2015)—research location in Bogor Regency. The software used is Qgis Desktop version 3.16.9. The method used in the research is spatial analysis, namely, overlaying forest cover data from 2011 and land cover in 2020. Bogor Regency still has a relatively sizeable natural forest cover, 36,595.04 ha. Natural forest cover is found in forest areas and other use areas. Most deforestation occurred in other use areas at 93.36%. Most forest conversion or deforestation occurs due to changes in forest cover to mixed Se-mak dryland agriculture.